PRINCIPLES OF USING NEW EDUCATIONAL TECHNOLOGIES IN TEACHING GEOGRAPHY TO SCHOOL STUDENTS - Nilufar Saydirasilovna Urinova (Galaxy International Interdisciplinary Research Journal, 2022)
The subject of "Geography" has a special role in expanding the effectiveness of the educational process in secondary schools. To do this, it is important to use non-traditional teaching methods in teaching the subject of "Geography". The article contains recommendations on the possibility of using non-traditional teaching methods in teaching the subject of "Geography".